Persepsi Orang Tua Tentang Pentingnya Pendidikan Tinggi Bagi Anaknya Di Dusun V Desa Batang Tumu Kecamatan Mandah Kabupaten Indragiri Hilir - Buyung Buyung; Charles Charles; Afrinaldi Afrinaldi; Salmi Wati (KOLONI, 2022)
The purpose of this study was to determine the perception of parents about the importance of higher education for their children in Hamlet V, Batang Tumu Village. And the use of this research is to provide scientific input and knowledge to parents or the public about the importance of higher education. and wasting time, fear of parents if their children stop going to college in the middle of the road due to lack of funds, many children who finished high school/equivalent who are unemployed. This type of research is a field research with a qualitative approach, namely describing a phenomenon that occurs according to the data in the field. Through observation, interviews, as well as describing and analyzing phenomena, events, social activities, beliefs, perceptions, thoughts of people individually, or in groups. From the research that has been done, it can be concluded that the perceptions of parents vary. There are those who think that higher education is good and a way to achieve their children's goals, there are parents who don't want to enter higher education because they are constrained by costs and are afraid to stop midway. There are also parents of the opinion and view that higher education or college is less important because there is no need to go to college which ends also looking for work and it is better to finish high school and go straight to work. Furthermore, parents consider it less important because their children are focused on studying religious knowledge, and religious knowledge can be obtained from Islamic boarding schools without having to continue to higher education or college. Keyword: Parental Perception, Higher Education